MENGGAGAS PENDIDIKAN TANPA KEKERASAN BERBASIS PEACE EDUCATION - stitlakbok, stitlakbok (Manajemen Pendidikan Islam STIT LAKBOK, 2021)
Education, which should display wisdom and compassion in the process, becomes a big problem if there are elements of undue violence in it.This study tries to examine and reopen cases of violence that occur in the world of education. By using a psychology-sociological approach as a tool of analysis, this study becomes interesting if it tries to take the chronological side of events and present solutions, of course from various aspects and perspectives.